ThermoEnergy Ammonia Recovery Process for Municipal and Agricultural Wastes - Alex G. Fassbender (The Scientific World Journal)
The Ammonia Recovery Process (ARP) is an award-winning, low-cost, environmentally responsible method of recovering nitrogen, in the form of ammonia, from various dilute waste streams and converting it into concentrated ammonium sulfate. The ThermoEnergy Biogas System utilizes the new chemisorption-based ARP to recover ammonia from anaerobically digested wastes. The process provides for optimal biogas production and significantly reduced nitrogen levels in the treated water discharge. Process flows for the ammonia recovery and ThermoEnergy biogas processes are presented and discussed. A comparison with other techniques such as biological nitrogen removal is made. The ARP technology uses reversible chemisorption and double salt crystal precipitation to recover and concentrate the ammonia. The ARP technology was successfully proven in a recent large-scale field demonstration at New York City’s Oakwood Beach Wastewater Treatment Plant, located on Staten Island. This project was a joint effort with Foster Wheeler Environmental Corporation, the Civil Engineering Research Foundation, and New York City Department of Environmental Protection. Independent validated plant data show that ARP consistently recovers up to 99.9% of the ammonia from the city’s centrate waste stream (derived from dewatering of sewage sludge), as ammonium sulfate. ARP technology can reduce the nitrogen (ammonia) discharged daily into local bodies of water by municipalities, concentrated animal farming operations, and industry. Recent advances to ARP enhance its performance and economic competitiveness in comparison to stripping or ammonia destruction technologies.